(untitled) (Cardiovascular Journal, 2017)
Background: This study was designed to assess the role of topically applied tranexamic acid in pericardial cavity in reducing post operative bleeding. Methods: This study is a non-randomized, double blinded, clinical trial, conducted in the Department of Cardiac Surgery, National Institute of Cardiovascular Diseases from January 2014 to December 2015 among the patients admitted for off pump coronary artery bypass (OPCAB) surgery. A total of 60 patients were recruited for the study and they were divided in two groups- 30 patients in tranexamic acid group (Group I) and 30 patients in placebo group (Group II). On completion of the grafting, before closure of the sternum tranexamic acid (2.5 g/25 ml) or placebo (25 ml of saline) diluted in 100 ml of warm saline (37 °C) was instilled into the pericardial cavity including the mediastinal tissues and left for 5 minutes. Total mediastinal bleeding and packed red cell transfusion were estimated in the postoperative period in both groups. Results: There was no significant difference noted in baseline demographic data, basic clinical characteristics and preoperative coagulation profile between the 2 groups (P > 0.05). Total mediastinal bleeding and packed red cell transfusion in group I and group II patients was 421.67±70.32vs 593.33±77.38ml, p<0.001 and 0.87±0.0.73 units vs1.77±0.57 units, p<0.001.No patient required reoperation for bleeding and there was no incidence of myocardial infarction (MI), thrombo-embolism, deep venous thrombosis (DVT) or stroke in none of the patients in either group. Conclusion: Topical application of tranexamic acid can significantly and safely reduce postoperative mediastinal bleeding. It also reduces whole blood transfusion requirements during immediate postoperative period among patients undergoing OPCAB surgery. Cardiovasc. j. 2017; 10(1): 52-55